2017
DOI: 10.1021/acs.cgd.6b01683
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Evolution of Crystal Size and Shape during Temperature Cycling and in the Presence of a Polymeric Additive Using Combined Process Analytical Technologies

Abstract: Crystal size and shape can be manipulated to enhance the qualities of the final product. In this work the steady-state shape and size of succinic acid crystals, with and without a polymeric additive (Pluronic P123) at 350 mL, scale is reported. The effect of the amplitude of cycles as well as the heating/cooling rates is described, and convergent cycling (direct nucleation control) is compared to static cycling. The results show that the shape of succinic acid crystals changes from plate- to diamond-like after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 46 publications
0
33
0
Order By: Relevance
“…45 Choice of Additives. Non-size-matched additives were chosen by reference to literature studies, where API crystal habit and growth conditions have been successfully controlled using large polymer additives, 14,15 and from a small available library of polymer additives. Building on the results of crystal face indexing studies, polymers with both hydrophilic (PEG-200) and hydrophobic (PPG-4000) properties were selected to allow further investigation of how hydrophilic/phobic components can affect the lovastatin needle thickness.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…45 Choice of Additives. Non-size-matched additives were chosen by reference to literature studies, where API crystal habit and growth conditions have been successfully controlled using large polymer additives, 14,15 and from a small available library of polymer additives. Building on the results of crystal face indexing studies, polymers with both hydrophilic (PEG-200) and hydrophobic (PPG-4000) properties were selected to allow further investigation of how hydrophilic/phobic components can affect the lovastatin needle thickness.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Temperature cycling experiments were first carried out in pure ethyl acetate solution; such methods have previously been shown to influence API crystal shape. 15 To investigate this, the effect of moving to a nonevaporative crystallization method on the lovastatin crystal morphology must first be assessed. Using a combination of literature solubility 50 and experimental solubility data (Figure 6) as a guideline, test experiments were first carried out at concentration levels of 4.6%, 3.2%, 2.2%, and 1.6% m/m to allow the optimum conditions to be selected.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lovastatin is widely known to exhibit a needle-like habit 49 that causes problems with processing and manufacturing of API [49][50][51][52][53][54][55][56][57][58] during filtering 58 and due to poor flow properties. 59 This morphology is known to arise from solvent interactions leading to slow growth of various facets.…”
Section: Discussionmentioning
confidence: 99%
“…Different crystal morphologies directly affect their performance and physical properties as well as processing. Generally, crystals having a smooth surface and an approximately spherical shape have better dispersibility and lower sensitivity than elongated needle‐like crystals or dendritic irregular crystals . For example, Liu et al found the spheroidized 1,3,5,7‐tetranitro‐1,3,5,7‐tetrazocine (HMX) with a higher initial temperature and better thermal stability than the feedstock.…”
Section: Introductionmentioning
confidence: 99%